Outcomes of spinal bracing and its associated factors among adolescents with idiopathic scoliosis in Sri Lanka- A lower middle-income country - Samitha Samanmalee Gowinnage; Dilani Vithanage; Duminda Munidasa; Pasyodun Koralage Buddhika Mahesh (Journal of Orthopaedic Reports)
Purpose: Customised Boston brace is used for controlling the curve progression in Adolescents with Idiopathic Scoliosis (AIS). This study aimed to describe the effectiveness of the Boston brace in controlling curve progression in AIS in a premier rehabilitation center in Sri Lanka. Methods: This retrospective study included patients with AIS with a primary curve between 200 – 450 and bone maturity at Risser sign 4 or below at the time of brace prescription. Having completed the brace treatment was an inclusion criterion. After reviewing 200 clinical records, 35 patients with eligibility criteria were selected. Data were collected through review of retrospective medical records and with prospective follow-up phone calls. Results: The sample consisted mostly of females (n = 23, 65.7 %) who were post-menarche, with a mean Risser stage of 2.63 (SD = 1.37). The mean in-brace correction rate was 27.34 % (SD 16.19), and the daily brace-wearing time was 16.69 h (SD 5.46). Successful treatment outcomes were achieved in 77.2 % of adolescents. In 12, primary curves decreased, in 8 it increased > 50, and in 15, it remained unchanged (0–5°). Treatment success was significantly associated with primary curves located in the thoracolumbar or lumbar regions (p = 0.047) and wearing braces for 18 h or more per day (p < 0.001). Conclusion: Individually customized Boston brace is effective in stabilizing curve progression in AIS patients, with increased success in thoracolumbar and lower lumbar curvatures among compliant patients.